Influence of Al doping on the structure and properties of Fe2O3 thin films: high transparency, wide band gap, ferromagnetic behavior. (25th June 2019) - Sharmin, Mehnaz; Podder, Jiban
Abstract: This paper presents a detailed study of structural, morphological, optical, transport and magnetic properties of aluminum (Al) doped ferric oxide (Fe2 O3 ) thin films deposited onto glass substrates at 350 °C by spray pyrolysis technique. Al concentration was varied from 0 to 10 atomic percentages (at%). The x-ray diffraction patterns of Al doped Fe2 O3 thin films showed the corundum structure with the predominant (104) peak. In scanning electron micrographs, the surfaces of the Al doped Fe2 O3 thin films were observed to be formed of nanoparticles. Al doped Fe2 O3 thin films were transparent in the visible to near infrared region. Transmittance and optical band gap of Al doped Fe2 O3 thin films increased with the rise of Al concentration up to 6 at% and then decreased for the 8 and 10 at% Al concentrations. Al doped Fe2 O3 thin films showed n-type electrical conductivity with high mobility and Hall coefficient. Electrical resistivity of Al doped Fe2 O3 thin films varied from 5.67 × 10 5 to 8.92 × 10 5 Ω-cm and carrier concentration was found between 1.56 × 10 17 and 8.64 × 10 17 cm −3 . Hysteresis loops of Al doped Fe2 O3 thin films recorded at room temperature matched with the nature of soft ferromagnetic materials and the saturation magnetization decreased with Al concentration in Fe2 O3 thin films.